RE-STRUCTURING PAKISTAN’S SOCIAL SECURITY NETWORKS: AN INSTITUTIONAL AND GOVERNANCE PERSPECTIVE (Contemporary Journal of Social Science Review, 2025)
The social security environment in Pakistan has developed as a fragmented and disjointed landscape that has created vast gaps in coverage, is focused on accuracy, institution coordination and sustainability. Historically, major schemes like Zakat system, Employees Old age benefits institution (EOBI), Workers Welfare Fund (WWF), and the Benazir Income support programme (BISP) have operated in isolation leading to duplication, administrative inefficiencies and unequal cover to the vulnerable populations[i]. Over the past few years, there has been an effort to combine, automate, and rationalise delivery of social protection under the Ehsaas framework but the problems of fragmentation, political disjunction, lack of sufficient funding, and poor governance persist. This paper has carried out a meta-analysis of 25 peer-reviewed articles, which emphasize empirical data on social safety nets in Pakistan, the mechanism of governance, targeting outcomes, institutional roles, and regional models. The meta-analysis defines five common themes, which are fragmentation of institutions, inadequate coverage, weak fiscal sustainability, absence of integrated databases, and political instability. The results of the frequency show that 84% of studies indicate the weakness of governance, 72% of studies refer to fragmentation, and 68% to fiscal unsustainability. The article suggests a restructuring of the paradigm based on a digital integration, coordinated federal-provincial development, lifecycle based social protection, and institutional redesign to guarantee predictability, openness, and long-term sustainability.